2022
DOI: 10.24018/ejbmr.2022.7.5.1627
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effect of Fundamental and Maturity Factors on Yield to Maturity of Corporate Bonds Traded on the Indonesia Stock Exchange in 2020

Abstract: The volume of corporate bond issuance in Indonesia has fluctuated from 2015-2020 following the economic developments. The Covid 19 pandemic in 2020 caused declining in companies issuing bonds. The pandemic led a big impact on the bond market. Low key interest rates decrease the return obtained in bond investment. The economic slowdown has pushed the central bank of Indonesia cut the key rates from 5% to 3.75% in 2020. The lower key rates will cause an increase in bank loans then the government can control econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…A picture of the comparison of how many short-term assets are owned by an industry with the amount of current debt held by the industry is called the current ratio [6]. Calculating the industry's ability to pay off its short-term obligations will soon be due for payment using the current ratio and the total short-term assets available.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A picture of the comparison of how many short-term assets are owned by an industry with the amount of current debt held by the industry is called the current ratio [6]. Calculating the industry's ability to pay off its short-term obligations will soon be due for payment using the current ratio and the total short-term assets available.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Various studies reveal that the current ratio is a predictor that can be seen in determining whether an enterprise has high or low value in the eyes of investors. Studies conducted [3][4][5][6] found that going up or down did not have a resulted on stock prices, whereas in the study [7] stated that positive resulted on stock revenues.…”
Section: Introductionmentioning
confidence: 99%
“…One of them is that the rate of return on bonds is generally fixed so that it would minimize the threat of loss. Another reason is that the issuer was cancelled, and bond investors have the honour to prioritize other creditors (Fitriadi & Marsoem, 2022). Bond investors would earn returns at a rate called yield.…”
Section: Introductionmentioning
confidence: 99%